DOES THE TIMING OF MEDICAL TREATMENT OF PATENT DUCTUS ARTERIOSUS (PDA) HAVE AN IMPACT ON THE SUCCESS OF TREATMENT IN PRETERM INFANTS?. (18th May 2018) - Kaur, Sharandeep; Stritzke, Amelie; Soraisham, Amuchou
Abstract: BACKGROUND: Hemodynamically significant patent ductus arteriosus (hsPDA) is the most common cardiovascular problem of prematurity often treated with nonsteroidal anti-inflammatory drugs (NSAIDs-indomethacin and ibuprofen). There is limited data on the effect of postmenstrual age (PMA) at the time of start of treatment on response rates to NSAIDs in preterm infants with hsPDA. OBJECTIVES: The objective of our study was to examine the effect of PMA at the start of treatment on response to NSAIDs in hsPDA. DESIGN/METHODS: In this retrospective cohort study, we included infants with gestational age (GA) ≤ 32 weeks admitted to a tertiary NICU between January 2014 and December 2016, who had received one or more doses of NSAIDs for the treatment of hsPDA. Positive response (responders) to NSAIDs was considered if post treatment echocardiogram showed that PDA was either closed or small, and did not require further medical or surgical treatment. We compared baseline characteristics between responders and non-responders using univariate and multivariable logistic regression. RESULTS: A total of 183 infants received 257 courses (one, two and three courses in 183, 62 and 12 neonates respectively) of NSAIDs. Positive response rate was overall 60%, and 66%, 48%, and 50% for the first, second, and third course respectively. The baseline characteristics were comparable between responders and non-responders except for higher GA, birth weight (BW), and earlier (<14 days of life) start of NSAIDs in responders. After adjusting for BW, Apgar score and gender, GA at birth but not the PMA, was associated with positive response to NSAIDs (aOR 1.24, 95% CI 1.07, 1.42 for GA; aOR 0.92, 95% CI 0.79, 1.07 for PMA). Early NSAIDs treatment was associated with increased odds of PDA closure (aOR 1.95; 95% CI 1.00–3.8). CONCLUSION: Gestational age is the strongest predictor for response to NSAIDs in hs-PDA and PMA at treatment does not affect efficacy of NSAIDs.